Dengue in the Renal Transplant Population - A Single Center Experience. (July 2018) - Kenwar, Deepesh; Kallepalli, Vidyasagar; Sharma, Ashish; Singh, Sarbpreet; Singh, Navdeep; Kapoor, Kunal; Chamb, Sandeep
Abstract : Background: Dengue is caused by an Arbovirus transmtted by the mosuqitoes, Aedes aegypti and Aedes albopticus and occurs in seasonal epidemics causing high rate of complications and mortality. It is endemic in India. Renal transplant recipients in endemic areas or those who travel to endemic areas are at risk of developing dengue. Case serires of dengue infection in renal transplant recipients have been reported. Our aim was to study the impact of dengue in renal transplant recipients (RTR). Method: Between 1st June 2107 and 31st November 2017, 55 RTRs were screened for dengue using a combination of microELISA NS1 antigenen and specific Ig M testing when dengue was clinically suspected based typical presentation of fever and severe myalgia. Baseline haemogram, and biochemistry tests were monitored and mycophenolate dosage adjusted as per development of complications. Tacrolimus and steroid regimen were not changed. Granulocyte colony stimulating factor was given to the patients with absolute neutrophil count <1000. Results: 32 patients (M:F - 27:5) tested positive for dengue (NS1 n=32 IgM n=3) with mean age 37.2 years (range = 19 - 64) and mean post-transplant duration of 36.2 months (range = 0-168). Early post transplant dengue (<3 mo post transplant) was diagnosed in 4 patients of which 3 were diagnosed within 2 weeks of transplantation (immediate post transplant dengue).Presenting features were fever and myalgia (n=32 100%). leukopenia <4000(n=11, 34%) low platelets < 1, 00, 000 (n= 26 81%) and diarrhoea (n=5 15.2%). Graft dysfunction (>25% rise in baseline creatinine) was observed in 12 patients (37.5%). Of the 4 RTRs with early period dengue 1 expired due to dengue shock syndrome with renal failure, 1 had persistent renal dysfunction and 2 had adequate recovery of renal function. One RTR with late period dengue expired due to dengue shock syndrome and renal failure. Maculopathy (n=3) and encephalopathy (n=1) were noted only in the early period dengue patients Two patients required G-CSF and 2 patients received single donor platelets. Retrospective screening of donors of patients with immediate post transplant dengue revealed dengue in 2 donors. Screening for dengue was introduced into the pretransplant work-up and of 35 donor-recipient pairs 9 tested positive for dengue and were postponed till dengue resolved. Conclusion: Early post transplant dengue infection appears to be severe and associated with more complications. The role of immunosuppressive regimen modification is not defined and screening dengue should be a part of the pre-transplant work up in endemic areas during the dengue season.